Structural change and output volatility reduction in OECD countries: Evidence of the Second Great Moderation - Hasan Engin Duran (Journal of Economic Structures, 2019)
In this article, we provide new, novel evidence for a more recent structural break (in 2010) indicating a greater moderation of output volatility compared to the well-known break during the mid-1980s. The period of analysis runs from 1962Q2 to 2018Q3. It covers 26 OECD countries. In terms of methodology, it has mainly been used as the measures of conditional and unconditional volatility and procedures of structural break detection (Inclan-Tiao test and autoregressive conditional heteroscedasticity model). As a result, it has been found that output greatly stabilized following the structural break at 2010Q1 in the post-era of 2008/09 global financial crisis. Moreover, output stabilization is robustly evident for 24 (out of 26) OECD countries. From a political standpoint, it is implied that the Keynesian view may be influential in this moderation. Government expenditures and fiscal programs, regulations of financial markets against the sub-prime lending and limitations to trade of mortgage-backed securities might have been the main driver of stability. Rapid improvement of digitalization and technical productivity may be regarded as another relevant reason that might have contributed to the stabilization process.
Keywords: E32; F44; E00; 330; Great Moderation; Structural breaks; Volatility